Preparation and properties of polyvinyl alcohol (PVA) and hydroxylapatite (HA) hydrogels for cartilage tissue engineering - Yuan, F.; Ma, M.; Lu, L.; Pan, Z.; Zhou, W.; Cai, J.; Luo, S.; Zeng, W.; Yin, F. (Cellular and Molecular Biology, 2017)
A novel bioactive hydrogel for cartilage tissue based on polyvinyl alcohol (PVA) and hydroxylapatite (HA) were prepared, the effects of its component contents on the mechanical properties and microstructure of the hydrogel were investigated. The important properties of the scaffold composites, such as density, porosity, compressive modulus and microstructure were studied and analyzed through various measurements and methods. The biodegradability of hydrogel was evaluated by soaking the samples into artificial degradation solution at body temperature (36 - 37 oC) in vitro. Experimental results showed that the PVA/HA hydrogels had a density of 0.572 - 0.683 g/cm3, a porosity of 63.25 - 96.14% and a compressive modulus of 5.62 - 8.24 MP. The HA compound in the hydrogels enhanced the biodegradation significantly and linearly increased the rate of biodegradation by 2.3 - 8.5 %. The compressive modulus of PVA/HA exhibited a linear reduce to 0.86 - 1.53 MP with the time of degradation. The scaffold composites PVA/HA possess a high porosity, decent compressive modulus and good biodegradability. After further optimizing the structure and properties, this composite might be considered as novel hydrogel biomaterials to be applied in the field of cartilage tissue engineering.